Penentuan Nilai Optimum Konsentrasi KMnO4dan Minyak Jarak pada Kemasan Aktif Bioplastik - Ni Kadek Tia Putri Ana; Ni Luh Yulianti; I Putu Surya Wirawan (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
Active packaging is an innovative packaging concept to maintain quality and increase product shelf life where active compounds added to the packaging can interact with food products and the environment, so research on active packaging is worth dev eloping. This study aims to produce the most optimum combination of KMnO 4 concentration and castor oil concentration to produce bioplastic active packaging characteristics that are in accordance with SNI Standards and International standards, and to determ ine the mathematical model of tensile strength response, elongation, elasticity, using Response Surface Methodology (RSM). Data was processed using Design Expert ® 12 software. The results of testing and analysis obtained a quadratic model on the observed responses. KMnO 4 concentration of 1.75% and castor oil concentration of 1% was the optimum combination selected. The verification test results showed the actual value of tensile strength 18.56 MPa, elongation 0.02 % modulus young 659.15 MPa. The response o f the combination of KMnO4 concentration and optimum castor oil concentration has a desirability value of 0 . 751% indicating that 75.1% of the expected response criteria can be met.